Frazeološka podoba smrti v makedonskem in slovenskem jeziku - Mirčevska-Boševa, Biljana (Jezik in slovstvo, 2020)
The article deals with the phraseological image of death in Macedonian and Slovenian. Macedonian and Slovenian idioms related to the concept of death in terms of meaning and/or components are discussed. Based on a chronological treatment of death, the collected phraseological material is analysed and divided into three large groups (death is approaching, death, posthumous moments). The initial hypothesis of the paper is that such a chronological conceptualisation of death can be applied to both languages.
Keywords: death; frazemi; frazeologija; idioms; Macedonian language; makedonščina; phraseology; Slovenian language; slovenščina; smrt